Identifying Antidepressant Effects of Brain-Derived Neurotrophic Factor and IDO1 in the Mouse Model Based on RNA-Seq Data - Ren, Jing; Li, Chenyang; Wei, Songren; He, Yanjun; Huang, Peng; Xu, Jiangping (Frontiers in Genetics, 2022)
Deletion of brain-derived neurotrophic factor (BDNF) and upregulation of indoleamine 2,3-dioxygenase 1 (IDO1) are associated with depression severity in animals. The neurotransmitter hypothesis of depression at the transcriptomic level can be tested using BDNF- and IDO1- knockout mice models and RNA-seq. In this study, BDNF+/-, IDO1-/-, and chronic ultra-mild stress (CUMS)-induced depression mice models and controls were developed and the differentially expressed genes were analyzed. Further, the ceRNA package was used to search the lncRNA2Target database for potential lncRNAs. Finally, a protein-protein interaction network (PPI) network was constructed using Stringdb. In comparing the control and CUMS model groups, it was found that pathway enrichment analysis and ceRNA network analysis revealed that most differentially expressed genes (DEGs) were associated with protection of vulnerable neuronal circuits. In addition, we found the enriched pathways were associated with the nervous system development and synapse organization in the comparing the control and BDNF+/- model groups. When replicating the neurotransmitter disruption features of clinical patients, such comparisons reveal the considerable differences between CUMS and knockdown BDNF models, and the BDNF+/- model may be superior than to classic CUMS model. The data obtained in the present study implicated the potential DEGs and their enriched pathway in three mice models related to depression, and the regulation of ceRNA network-mediated gene in the progression of depression. Together, our findings may be crucial for uncovering the mechanisms underlying the neurotransmitter hypothesis of depression in animals.